Yarrowia lipolytica as a potential chassis for value-added products using a co-culture system and lignocellulose biomass-derived xylose - Naz, Tahira; Saeed, Muhammad Tariq; Umer, Zujaja; Safdar, Waseem; Mohamed, Hassan; Song, Yuanda; Zhao, Xiang Yu (Frontiers in Microbiology, 2026)
Yarrowia lipolytica, a versatile and oleaginous yeast, has garnered significant attention as a promising microbial chassis for producing a vast array of important metabolic products, including trace minerals, vitamins, amino acids, protein and peptides, carbohydrates, and single-cell oil (SCO), primarily in the form of saturated high-value lipids like cocoa-butter equivalents and mono-unsaturated fatty acids (MUFAs). The US FDA has designated Y. lipolytica as a “safe-to-use organism” and given it GRAS (generally regarded as safe) classification for the synthesis of EPA, citric acid, and erythritol. Co-culturing multiple interspecies microorganisms together has proven to be a feasible and comparatively more efficient strategy than monoculture to target the degradation of waste components as a substrate and boost the production of significant metabolites. In recent years, a great deal of research has been devoted to exploring the potential of this host for the biosynthesis of valuable compounds from a wide variety of strategies. Despite ongoing efforts to improve our understanding of xylose metabolism in this yeast, there has been a notable lack of research focused specifically on the biosynthesis of natural products using xylose as a precursor, which is the second most abundant sugar in lignocellulosic biomass. This review also explores recent advances in the genetic modification of Y. lipolytica to enhance its ability to assimilate xylose and produce various secondary metabolites by using xylose as a substrate.